Rectal Polyps in Children. Hospital San Bartolomé, 1984 - 1996 - Romero Rojas, Nery (2000)
OBJECTIVES: To determine the main characteristics of rectal polyps in children in our hospital. MATERIAL AND METHODS: We studied the main clinical and anatomopathological features of 58 cases of rectal polyps in children at Hospital San Bartolomd, from 1984 to 1996. RESULTS: All polyps were histologically of Juvenile type. Mean age was 5,5 - years - old; males were 43 cases (74%), females were 15 cases (26%). The commonest symptoms were rectal bleeding in 54 cases (93%) and tumors in 24 cases (41%). 13 of them sized less than 1 cm (22%), 29 between I to 1,9 cms.(50%), 11 (19%) between 2 to 2,9 cms and 5 sized 3 cms. Length of disease was between I to 6 months in 59% (34 cases), one patient had sudden onset and the longest term was 3 years. We found 57 cases (98%) of single polyps and in only one case was multiple and familiar. CONCLUSIONS: Rectal polyps were tumoral lesions frequent in children. Painless rectal bleeding was the most frequent symptom. Single lesions predominated and Juvenile type was the most common. Mean age was 6 - years old (range from 3 to 8 - years - old).